Studies of the genetic resources of common beans (Phaseolus vulgaris L.) in Armenia - Kirakosyan G.V.; Melyan G.H.; Vardanyan V.A.; Sarikyan K.M. (BIO Web of Conferences, 2025)
The research was conducted at the experimental station of the Scientific Center of Vegetable and Technical Crops of RA from 2021 to 2023. Over 15 determinant and semi-determinant varieties belonging to the Phaseolus vulgaris species, including climbing, semi-climbing, and vegetable cultivars, were studied. Among them, eight samples (Contender, Blue Lake, Tendergreen, Dragon Tang, SP-1, FL-2, SM-3, and SH-5) exhibited the highest complex positive indicators. The local Masisi banjarayin variety served as the control. Most of the studied bean cultivars can serve as raw materials for creating new breeding varieties, enriching the existing genetic base, and promoting cultivation based on biological, phenological, and economic factors. Notably, the Contender and SM-3 cultivars stood out for their high yield of green beans, providing an 18.8–19.5% yield increase compared to the control variety.